PERANCANGAN KAPAL BULK CARRIER 16500 DWT KECEPATAN 13 KNOT SEBAGAI PENGANGKUTAN KEBUTUHAN SEMEN DENGAN RUTE PELAYARAN SEMARANG - LAMPUNG - Siti Muawenah, (2020)
The bulk carrier ship is a vessel that is classified into a type of commercial vessel specifically designed to transport bulk or unpackaged loads. Cargo that can be transported by Bulk carrier vessels such as grains, limestone, iron ore, iron sand, coal, etc. With bulk carrier ship load , for loading or unloading Bulk carrier vessels using loading and discharging tools such as conveyor and grib Crane. The high needs of cement in Sumatra due to the construction of toll road development projects that will connect Lampung to ACEH. In addition, the increasingly growing public to consume coffee, especially robusta coffee making coffee producers increase their productivity that impact the growing needs of robusta coffee beans to produce coffee drinks with the best quality. The solution that allows to meet the needs of cement and robusta coffee beans increasing is with the help of the distribution of the outside area, to transport the charge is needed transportation mode that can transport the payload as efficiently as possible. Bulk Carrier ships can be a solution for the distribution of materials that are bulk, therefore the authors are surprising to design a bulk carriership. The ship's design is done using several methods: Comparison method, trial method, and literacy method. The ship design with the main size and the form coefficient are thus obtained. In this design obtained the main size of the ship dwt = 16500 ton, LOA = 139.35 m, LWL = 137.79 m, LPP = 133.78 m, B = 21, 96m, H = 12.18 m, T = 8.8 m speed = 13 knots. From the hydrostatic calculation obtained displacement = 21199.228 ton, Cb = 0.8. In the calculation of stability, the results showed that the bulk carrier has good stability because the point M is above the point G in all conditions. ToThe general plan picture,